PEMASARAN DAN BREAK EVEN POINT USAHATANI NANAS DI KECAMATAN MASBAGIK KABUPATEN LOMBOK TIMUR - Ni Luh Sri Supartiningsih; Anwar Anwar (JURNAL AGRIMANSION, 2023)
The purposes of this research are to: (1) find out the marketing of pineapples in the District of Masbagik, (2) find out the cost structure of pineapple farming in the District of Masbagik, (3) analyzing the break even point on Pineapple farming in District of Masbagik. The results showed that: (1) Pineapple marketing channel in the District of Masbagik pass through three channel, namely : the first marketing channel; Farmers – PPD – PAP, the second marketing channel; Farmers – PAP, the third marketing channel; Farmers – Merchant Retailer. (2) The cost structure of pineapple farming is the variable costs amounting to IDR 16,324,152/Hectares, fixed costs amounting to IDR 1,462,680/Hectares and total production costs amounting to IDR 17,786,832/Hectares. (3) The production break even point (BEP) is 2,359.16 Kg/Ha, price BEP is IDR 577.48/Kg and revenue BEP is IDR 2,713,035.48.